A study on resolving conflict resolution in Southeast Asia country / Marina Hashim and Nur Fazlin Aripin - Hashim, Marina; Aripin, Nur Fazlin (Faculty of Administrative Science and Policy Studies, 2013)
Southeast Asia countries comprise of ten countries which is Brunei, Cambodia, Indonesia, Laos, Myanmar, Malaysia, Philippines, Singapore, Thailand, Timor Lester and Vietnam. All these countries then grouped together under Association of South East Asian Nation called ASEAN. Even there are cooperation between them, the conflict still occurred between one country to another country in this region. This study was conducted to identify the conflict that occurred in Southeast Asia countries and whether the conflict is being resolved or not. This study focused on the conflict in the Southeast Asia and a total of 44 conflicts have been used in completing this study. The main objective of this study is to determine whether different in category of conflicts can affect the resolving of the conflict. The statistical techniques used in this study are descriptive statistic and also chi-square test for goodness of fit. This study revealed that most of the conflicts occur in Southeast Asia countries are come from border conflict that comprise of land and maritime border. Other than that, this study also had identify the method that frequently used by countries in solving the conflict between them. The method that mostly been apply is resolving the conflicts is others method that included bilateral, meeting and many more.